How to dress a fish - Kerstetter, Abigail, author; Beachy-Quick, Dan, advisor; Dungy, Camille, committee member; Swensen, Thomas, committee member (Colorado State University. Libraries, 2016)
In 1901, my great-grandfather, Michael Chabitnoy, an orphan and full-blooded Aleut, was sent to the Carlisle Indian School in Pennsylvania, far removed from his Alaska Native heritage. He died shortly after my grandfather was born, and as a result, my family grew up knowing very little about the history and culture of the Aleut, though we’ve benefited from the Alaska Native Claims Settlement Act. This practice of boarding schools and displacement was common in the early twentieth century, but is glossed over in American history, as are the effects of this history on Natives today. As a result of early and brutal contact and relocation practices, much Aleut culture has been lost. This work seeks to redefine history through family, Aleut culture, and story to address questions of the relationship of culture, place, and the individual. In these poems I combine research into early encounters of the Russians with the natives of the Aleutian Islands, Aleut culture and traditional stories, and archived student records of my great-grandfather from the Carlisle Indian School with influence by the work of contemporary poets, native and non-native, that I have read closely while at CSU to explore family history and the Aleut culture as well as questions of the relationship of culture, place, and the individual and how language can reflect and remake experience and meaning. Heavily influenced by research and documentary poetics, this work seeks to provide witness to and understanding of the Aleut. This work is significant because it attempts to realize the potential effectiveness of using poetry as an act of witness and tool for social change. It demonstrates how language is capable of shaping one’s experience of the world, and how language can thus ultimately reshape one’s understanding of that experience. Through poetry, it examines the history and culture of a specific people, the Aleut of Alaska, as well as the history of the Native American experience on a more inclusive level through examining the history and experience of the Carlisle Indian School and modern complexities of Native identity. By incorporating excerpts from my great-grandfather’s student records, borrowing language from early ethnologies, and engaging with traditional Unangan storytelling motifs, it engages with documentary poetics to give witness not only to the treatment this people has already endured, but also through the incorporation of the Alutiiq language and traditions to give testimony to a people that persists today. Its interrogation of history and identity emphasizes the complexities of race and the politics behind every telling of history. This work is personally significant as a gesture of gratitude and act of reuniting with my ancestral culture.